Pandemic stress and the role of resources in expatriate–local interaction adjustment: an extension of Berry's model. Issue 2 (18th April 2022) - Reade, Carol; McKenna, Mark
Abstract : Purpose: The literature on expatriation rarely considers environmental stressors beyond cultural differences or interaction adjustment from the standpoint of host country nationals (HCNs). The authors develop a typology of expatriate–HCN interaction adjustment in response to a call to investigate the conditions under which pandemic stress facilitates cohesion or division among culturally diverse colleagues. Design/methodology/approach: The typology is based on Berry's acculturation model, developed with conservation of resources theory and extended with the dual-concerns problem-solving framework from the conflict management literature. Findings: The authors propose that expatriate and HCN perceptions of resource adequacy to cope with pandemic stress shape their choice of adjustment mode, and that contextual resources, including those provided by the organization, are critical. An Integration adjustment mode characterized by perceptions of adequate contextual resources and collaborative problem-solving is proposed to be most beneficial in the context of a pandemic to foster cohesion among culturally diverse colleagues, while a Separation mode characterized by perceptions of inadequate contextual resources and competitive problem-solving is proposed to foster division. Theoretical and practical contributions are provided. Originality/value: The study takes a novel interdisciplinary approach to develop a contextualized typology of interaction adjustment between expatriates and HCNs. It contributes to the literature on managing multinational enterprise stakeholders in high-risk environments and offers insights into the formulation of international HRM policies and practices during a pandemic that are applicable to other high-risk contexts.